Spectral distribution of photoelectric quantum yield of thin-film Au-CdTe diode structure - Grushko, E.V.; Maslyanchuk, O.L.; Mathew, X.; Motushchuk, V.V.; Kosyachenko, L.A.; Streltsov, E.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
A study of the Au/CdTe Schottky diodes fabricated by vacuum evaporation of
a semitransparent Au layer over an electrodeposited CdTe thin film is reported. The
theoretical model of the photocurrent spectra for an Au/CdTe Schottky diode based on
the continuity equation and incorporating the surface recombination losses does not
explain the measured spectra in the entire range of wavelengths, particularly the abovementioned
decay in the short-wavelength region. The satisfactory description of the
measured spectra is achieved by proposing a model, in which the surface recombination
along with the Schottky effect resulted in the presence of a dead layer in the space-charge
region is taken into account. By varying the parameters such as uncompensated carrier
concentration and carrier lifetime, the above model can explain the actual photoresponse
spectra.